Impact of the Educational Boost Your Brain and Memory Program Among Senior Living Residents. (December 2017) - Nicholson, Roscoe; O'Brien, Catherine
This random assignment waitlist control intervention study examined an implementation of the educational Boost Your Brain and Memory cognitive fitness intervention in 12 senior living organizations. Older adult participants ( n  = 166) completed measures of brain health knowledge, use of memory techniques, physical and intellectual activity, and mindfulness, at baseline and after the intervention group's completion of the course. Changes in knowledge scores and in self-reported physical and intellectual activity increased significantly more for intervention participants than for waitlist controls at the conclusion of the course. There were no significant changes between the groups in mindfulness or use of memory techniques. This suggests that in senior living settings Boost Your Brain and Memory is effective in educating participants about brain healthy behaviors and in motivating behavioral change in the areas of physical and intellectual activity.